Alfred Wiener and the making of the Holocaust Library - Barkow, Ben 1956- (Parkes-Wiener series on Jewish studies, 1997)
A catalogue of the suffering inflicted upon the the Jewish people was already in its 10th year of compilation by the time the Nazis held the Wannsee conference in 1942. This book tells how the Holocaust Library began.